Jesus talks to the Samaritan woman A dialogic analysis - Rule, Peter (2024)
The contemporary world is characterised by the dehumanisation of "the other" on multiple grounds. Jesus’ encounter with the Samaritan woman (John 4:1-42) sheds light on his attitude towards, and his engagement with her as a conventional "other" for Jews. This article aims to explain their dialogic encounter as an informal teaching and learning event against the backdrop of Jew-Samaritan relations and the status and roles of women in New Testament times. It uses the conceptual framework of diacognition, drawing on the notions of dialogue, position, and cognition to conduct an analysis of the episode as a learning event. It finds that the encounter enables the Samaritan woman to recognise Jesus asprophet and Messiah and transforms her conventional female positions to those of partner in dialogue, agent,and apostle. It thus challenges the "othering" of outsiders in contemporary church and society and affirms the leadership and agency of women.
Keywords: Dialogue; Jesus; Position; SAMARITAN women